Effect of 24 Weeks of Statin Therapy on Systemic and Vascular Inflammation in HIV-Infected Subjects Receiving Antiretroviral Therapy - Eckard, Allison Ross; Jiang, Ying; Debanne, Sara M.; Funderburg, Nicholas T.; McComsey, Grace A. (The Journal of infectious diseases, 2014)
Background. Human immunodeficiency virus (HIV)-infected individuals are at increased risk of cardiovascular disease (CVD) due in part to inflammation. Statins decrease inflammation in the general population, but their effect during HIV infection is largely unknown. Methods. This is an ongoing randomized, double-blinded, placebo-controlled trial to evaluate the effect of statin therapy on inflammatory markers during HIV infection. Subjects received rosuvastatin 10 mg daily or placebo for 24 weeks. Subjects were receiving stable (>12 weeks) antiretroviral therapy and had a low-density lipoprotein (LDL) cholesterol level of ≤130 mg/dL and evidence of heightened immune activation or inflammation. This was a prespecified interim analysis. Results. A total of 147 subjects were enrolled (78% were male, 70% were black, and the median age was 47 years). By 24 weeks, LDL cholesterol levels had decreased in the statin group, compared with an increase in the placebo group (-28% vs + 3.8%; P < .01). A 10% reduction in the lipoprotein-associated phospholipase A₂ (Lp-PLA₂) level was seen in the statin group, compared with a 2% reduction in the placebo group (P < .01). In multivariable regression, receipt of statin treatment and having a nadir CD4⁺ T-cell count of ≤100 cell/µL were the only statistically significant predictors of a decrease in Lp-PLA₂ level. Markers of systemic inflammation did not change significantly between groups. Conclusions. Twenty-four weeks of rosuvastatin therapy significantly decreased the level of Lp-PLA₂, a vascularspecific, inflammatory enzyme that predicts cardiovascular events in the general population. Statins may hold promise as a means of attenuating CVD risk in HIV-infected individuals by decreasing Lp-PLA₂ levels.